Comprehensive analysis of shared genetic loci between hippocampal volume and schizophrenia. (October 2022) - Li, Zongchang; Chen, Xiaogang
Highlights: Three shared genetic loci were identified between hippocampal volume and schizophrenia. Two lead SNPs have opposite effect directions on the increased schizophrenia risk and greater hippocampal volume. The majority of functional SNPs may play roles via their regulatory effects. Abstract: Schizophrenia and hippocampal volume exhibit a genetic correlation, but the underlying genetic mechanisms remain unclear. Here, we investigated the shared genetic variants in schizophrenia and hippocampal volume using the largest genome-wide association studies (GWASs) data. We identified three genetic loci associated with both schizophrenia and hippocampal volume. Functional annotation analysis suggested that shared genetic variants play a major role via the regulatory effect on gene expression. Expression pattern analyses showed that candidate genes have a spatiotemporal and cell-specific expression pattern across human brain development. These findings provided deeper insights into the genetic mechanisms underlying hippocampus and schizophrenia risk.